History of electrification in Tashkent during 1914–1918 years - Zokirjon Saidboboev; Gulzora Saidboboeva; Obidjon Jaynarov; Tulkinjon Kholiyarov; Sharofat Jiyanbekova (Історія науки і техніки, 2025)
After the colonization of the Turkestan region by the Russian empires in the second half of the 19th century, the tsarist authorities chose the city of Tashkent as the political, administrative and military center of the entire region. This was primarily due to Tashkent's trade and economic superiority over other cities, and secondly, the city's location in the central part of the country and its strategic importance. Although the industrial sectors were poorly developed, work began on the construction of power plants to illuminate the city streets and operate small manufacturing enterprises. The main focus was on Russian and foreign capital, and the initial projects were not implemented due to the bureaucratic system. Although the number of power plants operating in Tashkent increased somewhat in 1914–1917, they were used only for lighting buildings and streets of social importance, not for industrial purposes. By 1914, the Russian Empire ranked 8th in the world in terms of electricity production, with 14 kWh of electricity per capita in the central parts of the empire, while in Tashkent this figure was only 1 kWh per capita, indicating that the metropolis's attention and fundamental interests were directed to other things, rather than the development of the city's socio-economic sectors. Although the participation of the Russian Empire in the First World War gave impetus to the increase in production in the food, textile, and military industries, there were no noticeable changes in the energy sector. In particular, although attention was somewhat increased in Tashkent in 1914–1918 to the construction of power plants, financial difficulties for investors and the complex political changes of the time negatively affected the number of people at the helm of this work, which led to the postponement of planned work. Economically, Tashkent and its surroundings, as an industrial-agrarian region, have the potential to introduce various infrastructure systems, have vast natural raw material reserves, and have all the conditions for the construction of hydroelectric power stations, but these natural opportunities have not been fully utilized.